Medical online : java peer to peer based medical collaboration and communication system for the medical community [compact disc] - 452628 Ramesh Rabindren Rabindran (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering (Telecommunication)) - Universiti Teknologi Malaysia, 2002